The Role of Tomato WRKY Genes in Plant Responses to Combined Abiotic and Biotic Stresses - Bai, Yuling; Sunarti, Sri; Kissoudis, Christos; Visser, Richard G. F.; van der Linden, C. G. (Frontiers in Plant Science, 2018)
In the field, plants constantly face a plethora of abiotic and biotic stresses that can impart detrimental effects on plants. In response to multiple stresses, plants can rapidly reprogram their transcriptome through a tightly regulated and highly dynamic regulatory network where WRKY transcription factors can act as activators or repressors. WRKY transcription factors have diverse biological functions in plants, but most notably are key players in plant responses to biotic and abiotic stresses. In tomato there are 83 WRKY genes identified. Here we review recent progress on the function of these tomato WRKY genes and their homologs in other plant species, such as Arabidopsis and rice, with a special focus on the involvement of WRKY genes in response to abiotic and biotic stresses. In particular, we pay attention to the role of WRKY genes in plant responses to a combination of abiotic and biotic stresses.